Phlebotomine sandflies (Diptera: Psychodidae) in Governador Valadares, a transmission area for American tegumentary leishmaniasis in State of Minas Gerais, Brazil Flebotomíneos (Diptera: Psychodidae) em Governador Valadares, área de transmissão de leishmaniose tegumentar americana no Estado de Minas Gerais, Brasil - Ricardo Andrade Barata; Gustavo Fontes Paz; Marcela Cardoso Bastos; Roberta Christiane Oliveira Andrade; Daniela Campos Mendes de Barros; Fabiana Oliveira Lara e Silva; Érika Monteiro Michalsky; Aimara da Costa Pinheiro; Edelberto Santos Dias (Sociedade Brasileira de Medicina Tropical (SBMT), 2011)
INTRODUCTION: A study on the phlebotomine sandfly fauna was carried out in an endemic area for American tegumentary leishmaniasis in the municipality of Governador Valadares, in the State of Minas Gerais, Brazil. METHODS: Captures were undertaken using HP light traps in four districts, on three nights per month, for one year (from January to December 2008). Correlations between climatic factors (temperature, relative air humidity and rainfall) and the numbers of sandflies collected was observed. RESULTS: 5,413 phlebotomine specimens were caught and were identified as belonging to 12 species. Of these specimens, 2,851 (52%) were females and 2,562 (48%) were males. CONCLUSIONS: Lutzomyia intermedia predominated (29.9% of the species caught), thus suggesting that they were responsible for transmission of American tegumentary leishmaniasis, together with L. whitmani, which was also found in the area (4.3%). The presence of L. longipalpis (11.9%), the main vector for visceral leishmaniasis in Brazil, is an important finding, which makes rigorous entomological surveillance of the area necessary. INTRODUÇÃO: Um estudo da fauna de flebotomíneos foi realizado em uma área endêmica para leishmaniose tegumentar americana no município de Governador Valadares, no Estado de Minas Gerais, Brasil. MÉTODOS: Capturas foram feitas com armadilhas luminosas HP em quatro bairros, três noites por mês, durante o período de janeiro a dezembro de 2008. A correlação entre fatores climáticos (temperatura, umidade relativa do ar e pluviosidade) e o número de flebotomíneos coletados foi avaliada. RESULTADOS: Foram capturados 5.413 espécimes de flebotomíneos, distribuídos em 12 espécies, sendo 2.851 (52%) fêmeas e 2.562 (48%) machos. CONCLUSÕES: Lutzomyia intermedia foi predominante com 29,9% das espécies capturadas, sugerindo ser a responsável pela transmissão de LTA, juntamente com L. whitmani, que também foi encontrada na região (4,3%). A presença de L. longipalpis (11,9%), principal vetor de LV no Brasil, é um dado relevante tornando-se ...